Aspects of dorso‐ventral and proximo‐distal limb patterning in onychophorans. Issue 1 (January 2015) - Janssen, Ralf; Jörgensen, Mette; Prpic, Nikola‐Michael; Budd, Graham E.
SUMMARY Onychophorans (velvet worms) are closely related to the arthropods, but their limb morphology represents a stage before arthropodization (i.e., the segmentation of the limbs). We investigated the expression of onychophoran homologs of genes that are involved in dorso‐ventral (DV) and proximo‐distal (PD) limb patterning in arthropods. We find that the two onychophoran optomotor‐blind (omb) genes, omb‐1 and omb‐2, are both expressed in conserved patterns in the dorsal ectoderm of the limbs, including the onychophoran antennae (the frontal appendages). Surprisingly, the expression of decapentaplegic (dpp), which acts upstream of omb in Drosophila, is partially reversed in onychophoran limbs compared to its expression in arthropods. A conserved feature of dpp expression in arthropods and onychophorans, however, is the prominent expression of dpp in the tips of developing limbs, which, therefore, may represent the ancestral pattern. The expression patterns of wingless (wg) and H15 are very diverged in onychophorans. The wg gene is only expressed in the limb tips and the single H15 gene is expressed in a few dorsal limb cells, but not on the ventral side. The expression of wg and dpp at the limb tips is one of the three possible alternatives predicted by the topology model of arthropod limb patterning and is, thus, compatible with a conserved function of wg and dpp in the patterning of the PD axis. On the other hand, DV limb gene expression is less conserved, and the specification of ventral fate appears to involve neither wg nor H15 expression.